2021
DOI: 10.1002/for.2768
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural commodity price dynamics and their determinants: A comprehensive econometric approach

Abstract: We present a comprehensive modelling framework aimed at quantifying the response of agricultural commodity prices to changes in their potential determinants. The problem of model uncertainty is assessed explicitly by concentrating on specification selection based on the quality of short-term outof-sample forecasts (1 to 12 months ahead) for the price of wheat, soybeans and corn. Univariate and multivariate autoregressive models (autoregressive [AR], vector autoregressive [VAR] and vector error correction [VEC]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Following, for instance, Cuaresma et al (2018Cuaresma et al ( , 2021, leading indicators were used (CLI, amplitude adjusted, except for China, for which the normalised index was taken due to data availability). The U.S., G7, Euro area, and China were considered (OECD 2022).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Following, for instance, Cuaresma et al (2018Cuaresma et al ( , 2021, leading indicators were used (CLI, amplitude adjusted, except for China, for which the normalised index was taken due to data availability). The U.S., G7, Euro area, and China were considered (OECD 2022).…”
Section: Datamentioning
confidence: 99%
“…The selection of countries was made with a focus on the largest exporters and importers of commodities and to include so-called "commodities currencies". Indeed, according to the WTO (2022), amongst the largest commodities exporters and importers in 2020 and 2019 were Australia, Brazil, Canada, China, Germany, India, Japan, Russia, the United Arab Emirates, and the U.S. A similar set of variables was used by Cuaresma et al (2018Cuaresma et al ( , 2021, Gargano and Timmermann (2014), Chen et al (2010), Clements andFry (2008), andCashin et al (2004). These variables were transformed into logarithmic differences.…”
Section: Datamentioning
confidence: 99%
“…For example, Zhou (2021) used the ARIMA for modeling monthly corn prices in China during April 2019–February 2021 and forecasting the price in March 2021, and obtained good accuracy. Crespo Cuaresma, Hlouskova and Obersteiner (2021) studied auto-regressive models, VARs, VECMs and their variations and combinations for forecasts of different agricultural commodity prices that include those of corn. They found that market fundamentals and macroeconomic developments contribute systematic predictive information for the forecast purpose.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fernandez‐Diaz and Morley (2019) analyzed the interdependencies between agricultural commodity prices, crude oil prices, and macroeconomic variables, noting the increasing connection between crude oil prices and corn prices due to the promotion of biofuel policies. Cuaresma et al (2021) explored corn price prediction by incorporating market fundamentals, macroeconomic and financial development information, and climate variable data. The experimental findings revealed that the variables related to market fundamentals and macroeconomic development played a crucial role in the system forecast for out‐of‐sample prediction of corn prices.…”
Section: Introductionmentioning
confidence: 99%